2018
DOI: 10.1080/02673037.2018.1458288
|View full text |Cite
|
Sign up to set email alerts
|

Housing context and childbearing in Sweden: a cohort study

Abstract: Previous research has established the link between individuals' housing characteristics and their childbearing behavior. This study contributes to this literature by examining the association between first, second and third parity transitions and housing tenure and type. The study design distinguishes between owner-occupied apartments, rental apartments and owner-occupied detached houses. This study also uniquely takes into account individual housing histories in relation to later life fertility outcomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In future research, it would be interesting to further investigate how the effects of the socioeconomic factors on the second-child fertility intention differ between migrants and other social groups in China. For instance, unlike the positive effect of home ownership on fertility intentions observed in many other countries (Chudnovskaya, 2019;Felson & Solaún, 1975;Mulder & Billari, 2010;Palen, 1986;Sobotka et al, 2011), the revealed negative effect of home ownership in China's floating population is worth further exploration. In particular, we should examine whether the competing effect between home ownership and childbearing is peculiar to China's floating population.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In future research, it would be interesting to further investigate how the effects of the socioeconomic factors on the second-child fertility intention differ between migrants and other social groups in China. For instance, unlike the positive effect of home ownership on fertility intentions observed in many other countries (Chudnovskaya, 2019;Felson & Solaún, 1975;Mulder & Billari, 2010;Palen, 1986;Sobotka et al, 2011), the revealed negative effect of home ownership in China's floating population is worth further exploration. In particular, we should examine whether the competing effect between home ownership and childbearing is peculiar to China's floating population.…”
Section: Discussionmentioning
confidence: 94%
“…Individuals have housing preferences and constraints, which they balance with their fertility intentions, childbearing, and family formation (Chudnovskaya, 2019). Several housing characteristics have been identified as important factors underlying fertility intentions, including housing security and housing tenure (i.e., rented or owner-occupied; Mulder & Wagner, 2001;Vignoli, Rinesi, & Mussino, 2013), type of housing (i.e., multifamily vs. single-family dwelling; Chudnovskaya, 2019;Kulu & Steele, 2013), affordability of housing (Clark et al, 1994), access to the housing market (Mulder & Billari, 2010), and housing conditions such as size and location (Kulu & Boyle, 2009;Ström, 2010). Housing type refers to a residence being a detached home (also known as a villa, a single-family house, or a one-family residence) or an apartment (or an alternative multifamily dwelling such as a townhouse or terrace housing) in the western context (Kulu & Vikat, 2007).…”
Section: Home Ownership and Fertility Intentions Among China's Floamentioning
confidence: 99%
See 3 more Smart Citations